An Analysis of Investment Trends, Innovation and its Impact on Cabotage and Local Content Regime: Nigerian Experience from Businesses in Oil and Gas and Maritime Industries - Adeyemi, Omolade S.; Olubiyi, Timilehin O. (ABUAD Journal of Social and Management Sciences, 2024)
This study looks into how Nigeria’s oil and gas and maritime industries are affected by laws against cabotage and local content, with particular attention to employment rates, investment trends, technological developments, and communication. The study adopts the quantitative survey methodology. The target population comprises 358 oil and gas and maritime industries’ employees. Stratified random sampling was adopted to size the population into strata. Data was collected through a closed-ended structured questionnaire. The study used the primary and secondary data sources. The study examines the effects of local content and cabotage regulations in the two sectors, evaluating theories about employment rates, innovation, and investment trends. The result showed that there was a positive and significant effect of investment trend and innovation on cabotage law in the oil and gas industry in Nigeria (t-statistics (43.312) > critical value (0.000). Also, the study revealed that there was a positive and significant effect of investment trends and innovation on local content law in the oil and gas and maritime industry in Nigeria (t-statistics (48.491) > critical value (0.000). The findings show a strong positive correlation between compliance with these regulations and investment patterns. Turning barriers/obstacles into opportunities has proven to need effective innovation. The study recommends that policy improvement, improved innovative capacity, industry cooperation, monitoring, and enforcement will help improve compliance with the regulations and enhance investment patterns/innovation.